2010
DOI: 10.1089/end.2009.0200
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Glutaraldehyde for Completely Sutureless Laparoscopic Heminephrectomy in a Survival Porcine Model

Abstract: Introduction: Laparoscopic partial nephrectomy (LPN) has not received widespread clinical application because of its technical challenge. Bovine serum albumin glutaraldehyde (BSAG) is a hemostatic agent that is independent of the clotting cascade. We evaluated the use of BSAG as the sole agent for parenchymal and collecting system closure during LPN in a survival porcine model. Methods: Eighteen pigs underwent hilar clamping and LPN by longitudinal excision of the lateral one-third of the right kidney. The ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…To avoid intracorporeal suturing and additional loss of the functional renal parenchymal suturing edge, sutureless techniques have also been developed for LNSS using hemostatic agents and modalities such as glues, bolsters, lasers, and electrocoagulation. 12 , 13 , 19 , 20 However, sutureless techniques have only been reported in isolated case series or limited cases with comparison of knot-tying suture repair. 12 , 13 , 21 Although the feasibility of such techniques has been previously demonstrated in the literature, the long-term oncological outcomes, specific indications, and technical tips remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid intracorporeal suturing and additional loss of the functional renal parenchymal suturing edge, sutureless techniques have also been developed for LNSS using hemostatic agents and modalities such as glues, bolsters, lasers, and electrocoagulation. 12 , 13 , 19 , 20 However, sutureless techniques have only been reported in isolated case series or limited cases with comparison of knot-tying suture repair. 12 , 13 , 21 Although the feasibility of such techniques has been previously demonstrated in the literature, the long-term oncological outcomes, specific indications, and technical tips remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Even in expert hands, rates of urine leakage and hemorrhage are not negligible (19). Despite the development of adjunctive hemostatic agents, none have proved to offer complete hemostasis by themselves (19). In this paper, we demonstrated that sutureless LPN with TISSUCOL Âź can reduce warm ischemia and total operative times as well as preserve kidney function, without severe complications when compared with standard suturing LPN.…”
Section: Discussionmentioning
confidence: 91%
“…LPN is increasingly performed all over the world and constitutes a valid procedure for the management of small renal tumours, but some technical aspects still need to be improved. Even in expert hands, rates of urine leakage and hemorrhage are not negligible (19). Despite the development of adjunctive hemostatic agents, none have proved to offer complete hemostasis by themselves (19).…”
Section: Discussionmentioning
confidence: 99%
“…BioGlue is not a hemostatic agent and does not influence the clotting cascade; however, it has been shown in a number of human and animal studies to effectively maintain hemostasis during open or laparoscopic partial nephrectomy alone or in combination with suturing or other hemostatic agents. 6 – 8 …”
Section: Discussionmentioning
confidence: 99%